Labor Market Insiders or Outsiders? A Cross-National Examination of Redistributive Preferences of the Working Poor - Asaf Levanon (Societies, 2018)
Prior research on attitudes toward redistribution documents an association between one’s policy preferences and socioeconomic position, as well as an impact of welfare policy on the mean level of support for redistribution. Building on both traditions, the current paper aims to expand our understanding of the sources of public support for welfare policies by examining the role that social policy plays in shaping the policy preferences of the working poor. Building on the distinction between labor market insiders and outsiders, this paper examines whether preferences by the working poor more closely resemble those of non-poor workers or those of non-working poor individuals. Results from this study show that the degree of support for redistribution among the working poor is notably closer to the average degree reported by non-working poor individuals than the mean level reported by non-poor workers. Moreover, utilizing cross-national data from 31 countries in 13 different time-points between 1985 and 2010, the paper documents a much smaller preference gap between non-poor workers and the working poor and a higher overall level of support for redistribution in countries providing a greater degree of employment protection.